P85 Congenital syphilis in the UK: results from enhanced surveillance, 2010/11. (23rd May 2012) - Simms, I; Tookey, P; Goh, B; Lyall, H G; Evans, B; Ison, C
Abstract : Background: Since 2001, rates of congenitally transmissible syphilis have increased amongst reproductive age women. Concerns have been raised about the effectiveness of intervention which has been restricted by an absence of national surveillance data. In 2010, a 3-year study was established to provide an evidence-base for control strategies. Aim: To explore the epidemiology of congenital syphilis. Methods: The surveillance dataset consisted of returns to the British Paediatric Surveillance Unit, diagnoses made in genitourinary medicine clinics (GUMCAD) and laboratory reports. Infants diagnosed with congenital syphilis under the age of 24 months were included (detailed methodology at: http://www.rcpch.ac.uk/ ). Results: Between 1 February 2010 and 1 November /2011, 11 cases (male=9, female=2) of congenital syphilis were confirmed, all reported from England. Most infants (6/10) were born at over 37 weeks: median birth weight was 2910 g (range: 1340 g to 3690 g). Clinical presentation varied from asymptomatic (1) to acute, including severe anaemia, hepatosplenomegaly, rhinitis, oedema, thrombocytopaenia and skeletal damage. Median maternal age at delivery was 19 (range: 17–28). Many of the infants' mothers were White and came from the UK and Eastern Europe. Where maternal stage of infection was recorded, 4/7 presented with primary and 3/7 with secondary syphilis. One infection diagnosed late in pregnancy was the result of re-infection acquired after effective screening and management in the first trimester. All diagnoses were managed according to BASHH Guidelines. Conclusions: Congenital syphilis presents a complex social, clinical and public health problem. Antenatal screening is largely effective in controlling congenital syphilis but delivering effective health care to women who are marginalised in society and at-risk of acquiring congenitally transmissible syphilis represents an emerging challenge.